Highly sensitive and fast-responsive room-temperature LPG sensor based on hydrothermally synthesized MoTe2 - Singh, Ankit; Kumar, Avdhesh; Chaurasiya, Navin; Rani, Alka; Gupta, Monu; Yadav, B. C.; Singh, Manish Pratap (Frontiers in Nanotechnology, 2025)
In the current study, a highly efficient and affordable sensor for liquefied petroleum gas (LPG) that operates at ambient temperature was fabricated using a thin film through an easy and low-cost approach. To achieve this objective, MoTe2 was synthesized using a hydrothermal method. The synthesized material was characterized through powder X-ray diffraction (PXRD), Raman spectroscopy, Fourier transform infrared (FTIR) spectroscopy, field-emission scanning electron microscopy (FE-SEM), and energy-dispersive X-ray spectroscopy (EDS). According to the results of PXRD and Raman spectroscopy, a pure phase of layered MoTe2 with a hexagonal structure without any notable impurities was formed. The average crystallite size of the synthesized material is ∼37 nm. Raman spectroscopy and FTIR analysis revealed the presence of Mo–Te vibrational modes. The surface morphology reveals thin, wrinkled sheets with a crumpled topology having flake-like structures. The coexistence of Mo and Te elements was confirmed using the EDS study. The optimized sample was used to prepare the thin film using a spin-coating process. The sensing properties of the MoTe2-based thin film were investigated as a room-ambient sensor for various LPG concentrations below the lower explosive limit of 0.5–2.0 vol%. The best sensor responses were recorded at 2.0 vol% LPG, with a value of 137, and at 0.5 vol% LPG, with a value of 26. Moreover, a rapid response time of 8 s and a recovery time of 22 s were observed at 0.5 vol% of LPG. These rapid dynamics are attributed to the prompt interaction between LPG molecules and pre-adsorbed oxygen species on the film surface, enabling fast adsorption-desorption cycles at active sensing sites. The results highlight the potential of MoTe2 thin films as effective and scalable candidates for ambient LPG detection.